Oxyhydrogen Nanobubbles Suppress FoxP3 and Ki-67 Expression in a Wistar Rat Model of Hepatocellular Carcinoma - Natasya Adiba Zahrah; Sri Widyarti; Dyah Kinasih Wuragil; Wibi Riawan; Olly Indrajani; Ahmad Lubab; Aditya Tri Hernowo; Sutiman Bambang Sumitro; Aulanni'am (Jurnal Penelitian Pendidikan IPA, 2026)
HCC is difficult to treat due to its complex tumor microenvironment and the ineffectiveness of available therapies. Gas-based anticancer approaches are promising, but are hampered by instability and difficulties in targeted delivery. HHOnbs (containing hydrogen (H2), oxygen (O2), and low-dose hydrogen peroxide (H2O2) at the nanoscale) have been proposed to improve the stability and precision of gas-based therapies. This study aimed to investigate the effects of HHOnbs on the immunoregulatory marker FoxP3 and the proliferation marker Ki-67 in a Wistar rat model of HCC induced by diethylnitrosamine (DEN)/carbon tetrachloride (CCl4). The design used was a true experimental design. HHOnbs were administered intravenously. Liver tissue was assessed using immunohistochemistry to measure FoxP3 and Ki-67 expression. HHOnbs treatment significantly reduced FoxP3 and Ki-67 expression (p<0.05). FoxP3 is a marker of regulatory T cells (Tregs), which often inhibit antitumor immune responses. Its decrease indicates an increased immune response potential. Ki-67 is a marker of cell proliferation. Its decrease indicates the suppression of cancer cell growth. Further investigations are warranted to compare its efficacy with standard therapies, assess different treatment durations, and elucidate the underlying molecular signaling pathways.